New Integrals Arising in the Samara-Valencia Heat Transfer Model in Grinding - J. L. González-Santander (Journal of Applied Mathematics)
The Samara-Valencia model for heat transfer in grinding has been recently used for calculating nontabulated integrals. Based on these results, new infinite integrals can be calculated, involving the Macdonald function and the modified Struve function.